Bulletin 68 Electric Switches for Use in Gaseous Mines - H. H. Clark; R. W. Crocker (The National Institute for Occupational Safety and Health (NIOSH), 1913)
The purpose of the investigation discussed in this bulletin, one of a series dealing with the use of electricity in mines, was to study the various means and methods used to confine the flashes that occur when a switch carrying electric current is opened. The flash result- ing from the opening of a 250-volt direct-current circuit carrying more than half an ampere will ignite explosive mixtures of mine gas and air. An equally dangerous flash may be produced by even less cur- rent from a 500-volt circuit. Few mine electric circuits carry less than half an ampere when in use. The need of protecting the switches of such circuits in places where gas is likely to be present is therefore obvious. Two general methods have been proposed for preventing switching flashes from igniting gas surrounding the switch. One method is to inclose the switch in a casing provided with openings that are covered with wire gauze or otherwise designed and equipped for preventing the passage of flames from the interior to the exterior of the switch casing. Switches so protected are called explosion-proof switches. The second method is to immerse the switch contacts in oil to a depth sufficient to quench any flash that may occur when the switch is operated. Switches so protected are called oil switches. The success of the first method of protection depends upon the proper design and construction of the switch casing. It is essential to the successful operation of the second method that the switch contacts be surrounded by the proper kind of oil in good condition. There are several ways in which an oil switch may be deprived of its protective feature. The oil tank may not be filled or, if filled, the oil may leak out or be spilled. The oil tank may be removed (in some designs) and not replaced or through neglect the condition of the oil may become such that it is no longer an efficient protection. While such contingencies are not likely to occur, and although oil switches may be so designed that the loss of oil is not probable, nevertheless, as compared with oil switches, explosion-proof switches seem to